ESP vocabulary instruction: a comparison of CBI vs. GTM for Iranian management students - Ahmadi-Azad, Shima; Kuhi, Davoud (Penerbit Universiti Kebangsaan Malaysia, 2016)
Vocabulary learning is an essential part of the language learning process. This study aimed at investigating the effects of two different methods of English for Specific Purpose (ESP) instruction, namely, the Content-based Instruction (CBI) and traditional Grammar Translation Method (GTM) on Iranian ESP students’ technical vocabulary learning. To this end, two intact classes of specialized English for management students in Gowgan Azad University were randomly assigned into two groups (N= 29 participants in each), and their homogeneity was confirmed by Comprehensive English Language Test. Group A was instructed based on CBI, while group B was instructed according to GTM principles. The data were collected through a teacher made management vocabulary test which applied both as pre-test and post-test. Following a pre-test, the two groups received different instructions during 10 sessions, and then a post-test was given. The obtained data was analyzed using paired samples t-test to compare the effects of CBI and GTM on ESP vocabulary learning. The results indicated a significant propriety of CBI over GTM in improving vocabulary knowledge of the ESP students. Some justifications for this priority were discussed to be the ESP students’ more cognitive engagement and negotiation of meaning in a CBI based classroom.